THE COMPARISON ANALYSIS OF CONSUMER COMPLAINT AND SWITCHING BEHAVIOR FROM XL TO TELKOMSEL PRODUCT IN MANADO - Oroh, Friskia; Pangemanan, Sifrid S. (FEB Universitas Sam Ratulangi Manado, 2015)
Indonesia is one of the countries that experienced the most rapid growth in the mobile industry. The two examples of mobile industry are XL and Telkomsel. The objectives are to know if there is significant difference of consumer complaint and switching behavior between XL and Telkomsel. This research is a comparison type, by using quantitative method, in which use questionnaire as a tool to gather data and analysis. The hypothesis of this research is there is a significant difference of consumer complaint and switching behavior between XL and Telkomsel. The populations observed are those who are complaint and make a switching behavior between XL and Telkomsel in Manado with sample 100 respondents. This research analyzes about the compare means with independent samples T-test between XL and Telkomsel based on Technical, price/billing and miscellaneous problem.The result shows that are a mean different between XL and Telkomsel in terms of consumer complaint and switching behavior, and it are supported by level of significant.It is better for XL company management to improve the service quality for consumer, so the switching behavior can be decreased. Keywords: consumer complaint, switching behavior.